Study guides

☆☆

Q: What is answer to 27a-18b plus 9c?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

-6(a-3b-9c)

9

2ab - 6ac + 3b - 9c = 2a(b - 3c) + 3(b - 3c) = (2a + 3)(b - 3c).

9C = 234

Well I got this: 2c+7=9+6-7c+2c 2c+7=15-9c 11c+7=15 (add 9c) 11c=8 ( Subtract 7) 11---11 ( Divide 11) C=0.72

Related questions

-6(a-3b-9c)

It is: 6-11+5-8c+9c = c

9c is.

(12c5 - 18c3 + 9c) / (-3c) = -4c4 + 6c2 - 3

3a + 9 =3X(a + 3)

Yes; the factored form would be (9c+4)(9c+4) or just (9c+4)2 Since the two factors are the same, the beginning trinomial 81c2+72c+16 is a perfect square trinomial

9

2ab - 6ac + 3b - 9c = 2a(b - 3c) + 3(b - 3c) = (2a + 3)(b - 3c).

2ab - 6ac + 3b - 9c = b(2a + 3) - 3c(2a + 3) = (b - 3c)(2a + 3)

9C = 234

18 degrees, C

18 degrees, C

People also asked